Assessment on clinical value of prostate health index in the diagnosis of prostate cancer. (17th July 2019) - Zhang, Guangying; Li, Yanyan; Li, Chao; Li, Na; Li, Zhanzhan; Zhou, Qin
Abstract: In this study, we performed a comprehensive estimation and assessment for the clinical value of prostate health index (PHI) in diagnosing prostate cancer. Using the bivariate mixed‐effect model, we calculated the following parameters and their 95% confidence internals (CIs), including sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnostic odds ratio and symmetric receiver operator characteristic. Twenty eligible studies with a total number of 5543 subjects were included in the final analysis. The estimated sensitivity was 0.75 (95% CI: 0.70‐0.79) and the specificity was 0.69 (95% CI: 0.58‐0.83). The pooled area under the curve was 0.78 (95% CI: 0.74‐0.81). The combined positive likelihood ratio was 2.45 (95% CI: 2.19‐2.73) and the negative likelihood ratio was 0.36 (95% CI: 0.31‐0.43). The diagnostic odds ratio was 6.73 (95% CI: 5.38‐8.44). The posttest probability was 40% under the present positive likelihood ratio of 2.45. It seems there was no significant difference between Asian population and Caucasian population population in sensitivity and specificity. But the overlap of AUC 95% CI indicated that the diagnostic accuracy of PHI was slightly higher in the Asian population population setting than that in the Caucasian population population population (0.83 vs 0.76). Similarly, there was also overlap in AUC 95% CI, which suggested that sample size may be one of heterogeneity source. The PHI has a moderate diagnostic accuracy for detecting prostate cancer. The discrimination ability of PHI is slightly prior to free/total prostate‐specific antigen. It seems that ethnicity has an influence on the clinical value of PHI in the diagnostic of prostate cancer. Abstract : The prostate health index (PHI) has a moderate accuracy for detecting prostate cancer. The diagnostic ability of PHI is slightly prior to free/total prostate‐specific antigen. The ethnicity seems to have an influence on the diagnostic accuracy of PHI.